The Influence of Psychological Safety, Change Management Effectiveness and Inclusive Leadership on Employee Resilience in Multinational Companies - Ade Suhara; Haris Karyadi; Ahmad Nur Budi Utama; Nurlelasari Ginting; Fatimah Malini Lubis; Iwan Henri Kusnadi (Fakultas Ilmu Pendidikan Universitas Pahlawan Tuanku Tambusai, 2026)
In the current investigation, the researchers aim to examine the impact of psychological safety, right change management, and inclusive leadership on the resilience of employees in international firms. The need for this study arises from the global business environment, which is constantly changing and unpredictable, necessitating the employees to be highly resilient mentally. A quantitative explanatory approach was adopted in the research, and the data were obtained through a questionnaire administered to 180 employees in the Indonesian subsidiaries of international companies. The sampling technique applied in the data collection was purposive sampling. In addition, the data collected were analyzed using multiple linear regression after they had met the required conditions for validity, reliability, and classical assumptions. The findings indicate that psychological safety, change management effectiveness, and inclusive leadership positively and significantly influence employee resilience. One of the contributions of the research to the organization behavior literature is that it provides empirical evidence regarding the factors affecting employee resilience from the perspective of multinational corporations. The management can deduce the strategic implications of the study results in terms of the creation of a psychologically safe workplace, effective change management, and the application of inclusive leadership for the purpose of employee resilience and organizational sustainability enhancement.